Análise dos impactos do Pronaf na agricultura do Brasil no período de 2007 a 2016 - Jair Andrade Araujo; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This discussion paper analyzes the impacts of Pronaf on agriculture and livestock for the 26 Federative Units and the Federal District of Brazil in the period between 2007 and 2016. The Panel Auto Regressive Vector method was used to measure the effects of credit shocks offered by Pronaf, through the quantity and value added of the agriculture and livestock contracts, over the planted area; gross value of agricultural and livestock production and land productivity. By means of information from the Central Bank (BCB) and the Brazilian Institute of Geography and Statistics (IBGE), the results indicate that the impulse response of the planted area, the production value and the productivity of the land, to a credit shock generated a positive response over a period until they changed direction and converged to zero after the sixth period. However, there are conflicting results when the shock occurs in the number of Pronaf contracts for agriculture. It is concluded that Pronaf imposes selection bias and does not encourage the farmer to diversify his production, thus, promoting development and reducing rural poverty will be compromised and therefore needs to be restructured.
Keywords: J30; J38; Q19; 330; rural credit; farming; VAR in panel